The influence of israelites narratives in business research from islamic perspectives - Mhd. Sarif, Suhaimi (Zesdyzar Rokman Resources, 2015)
The narratives for business research from Islamic perspectives are from the primary sources, Al-Quran and Sunnah (traditions)of Prophet Muhammad (peace be upon him). Most business researchers are not proficient to use the primary references but to rely on narratives that are translated in English and other languages that are conversant with the researchers. The presence of Israelites materials in the translated narratives is inevitable, but this can have implications on the authenticity of the literature. The purpose of this paper is to explore the influence of Israelites or Israeliyat in the references used for Islamisation of human knowledge in business research. The study uses content analysis on the feedback given by selected scholars in Islamic studies who are familiar with the Israelites. There a few findings from this study. Firstly, the paper argues that Islamisation of human knowledge is to incorporate, integrate and imbue the existence human knowledge with Islamic philosophy that derived from Islamic references, particularly Al-Quran and Ahadith. Secondly, the paper argues that Islamic references contained Israeliyat elements which can be questioned in terms of its authenticity. Thirdly, scholars are not clear on to be part of the Islamisation of human knowledge in the presence of Israeliyat elements in the ahadith and seerah (history) of Islam. Fourthly, scholars are not competent to use Islamic references. The study recommends general guidelines for researchers in using the translated narratives for business research from Islamic perspectives.